Implementation of Project-Based Learning MBKM English Literature Study Program UIN Sunan Kalijaga on English Language Capacity Building at Madrasah Aliyah Diponegoro Yogyakarta - Lestari, Febriyanti; Fajri, Anisah Durrotul; Sari, Ulyati Retno (LinguaScopes: International Journal of Language Education, 2024)
English as an international language is very important for students to learn in madrasas. One of the problems that students often face when learning English is speaking competence. To overcome these problems, one of them can be taken by implementing Project-Based Learning (PBL). This study aims to determine the effect of PBL implementation on improving the English speaking capacity of MA Diponegoro students. In addition, this study also aims to determine the changes in the attitudes of MA Diponegoro students after the implementation of the PBL learning model. The source of data for this study is 23 students of Class X MA Diponegoro Yogyakarta, 2 students of the English Literature Study Program of UIN Sunan Kalijaga who have completed the previous TEFL Methodology course and in this study act as PBL teachers, as well as 2 lecturers and 1 alumnus of the English Literature Study Program as observers. This study uses an interactive analysis method in the process of analyzing students' English language capacity and attitudes during PBL and data collection techniques through observation, interviews and documentation over a period of 3 months. The results showed that of the 23 students, all experienced significant changes in English speaking capacity (fluency, pronunciation & accent, grammar, vocabulary and details), although none of the students had really reached the excellent level. It can also be concluded that the final product of PBL in the form of English speeches that are done in pairs, uploaded to the school's YouTube channel, competed and given awards have a positive effect on changing students' attitudes, where they become more confident in practicing English speaking, motivated to dare to be active in class, and comfortable working together to complete speech projects. This kind of PBL model has the potential to be developed for MBKM activities.